DISCRETE DYNAMICAL MACROMODELS AND THEIR USAGE IN ELECTRICAL ENGINEERING - Stakhiv, Petro; Kozak, Yuriy (International Journal of Computing, 2011)
An optimization approach intended for construction of macromodels of dynamic objects especially for electrotechnical systems is proposed in the paper. This approach is efficient because of its universality. A set of techniques to simplify optimization task needed for the identification of macromodels is considered. The specifics of the use of the mentioned approach for the creation of models for autonomous objects and prediction of dynamic processes are described. The test example of the macromodel construction for two-winding transformer using the considered approach is presented.